164 Urinary ALCAM as a novel biomarker for renal pathology in lupus nephritis. (April 2019) - Ye, Zhizhong; Ding, Huihua; Lin, Cheng; Dai, Min; Guo, Qiang; Shen, Nan
Abstract : Background: Lupus nephritis is one of the most common and severe complications of SLE affecting more than 60% patients. The management of lupus nephritis largely depends on renal histopathologic findings. Due to the invasive feature and complications of renal biopsy, it is significantly urgent to develop novel biomarkers to predict renal pathology. Methods: In this cross-sectional study, a total of 77 biopsy-proven active LN, 61 active SLE without LN75 inactive SLE patientsand 28 age and gender matched healthy controls were recruited. Urinary levels of activated leukocyte cell adhesion molecule (ALCAM) were determined by enzyme-linked immunosorbent assay in urine samples of the above-mentioned subjects. Renal histopathology was review by an experienced renal pathologist. Urinary ALCAM levels were normalized by urine creatinine. For active LN patients, all samples were collected at the time of renal biopsy. Results: Urinary ALCAM levels were significantly increased in active LN patients when compared to those in active SLE without renal involvement patients, inactive SLE patients, and healthy controls (figure 1 A). ROC analysis showed a good performance of urinary ALCAM in discriminating active LN from active SLE without renal involvementinactive SLEand healthy controls (figure 1 B). Further correlation analysis revealed a positive correlation between urinary ALCAM and general disease activity-SLEDAI score, as well as renal disease activity-rSLEDAI and SLICC-RAS (figure 2 A-C). Urinary ALCAM also correlated with lab parameters including 24 hour urine protein, hemoglobin, and complement 3 (C3) (Figure 2 D-F). More interestingly, we found a good prediction value of urinary ALCAM in renal histopathological findings. Urinary ALCAM levels were significantly increased in proliferative LN (Type III and IV) as compared to those in membranous LN Type V (Figure 3 ). It outperformed conventional biomarkers (anti-dsDNA antibody, C3, C4) in discriminating the two different types of LN. Urinary ALCAM levels correlated positively with activity index (AI) in renal histopathology, indicating a role in guiding clinical management of LN. Conclusions: Urinary ALCAM is a promising biomarker for predicting renal histopathological changes in LN, which may serve as a valuable surrogate of renal biopsy. These findings should be confirmed in a larger cohort to further validate the utility of urinary ALCAM as a biomarker. Funding Source(s): N/A